JUAN RAFAEL ALLENDE’S ¿WANDERINGS INTO THE CITY OF ‘MARBLE PALACES’ AND DELIGHTFUL CASSEROLES. SANTIAGO OF CHILE, 1880-1910. - Palma Alvarado, Daniel (Revista de Historia Social y de las Mentalidades, 2011)
This article deals with a chapter of the social and  urban history of Santiago de Chile, throughout  a period in which the city was subject of deep  changes that modified its colonial setting and  long lasting social relationships. Following  the sharpness of the satiric writer Juan Rafael  Allende, we look to the insuficiencies of the  urbanizing process, the new characters ocupying  the city’s squares and streets, as well as the  multiple entertainments animating the everyday  life of its inhabitants.
Keywords: Santiago de Chile; Juan Rafael Allende; satiric press; urban history